On Some Spectral Properties of the Energy Operator for an Infinite System in a Magnetic Field - Samoilenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
For systems in a magnetic field, we investigate the form sum of an infinite-dimensional energy operator perturbed by a potential. We also investigate changes in the spectrum of the energy operator in the case of its perturbation by a potential.